Problemy z granicami wypowiedzeń w polszczyźnie mówionej – uwagi wstępne - Szczyszek, Michał (Poznańskie Spotkania Językoznawcze, 2015)
The article discusses the problems associated with segmented into separate sentences the stream of spoken language. There are both: theoretical problems (what is utterance?, what are its boundaries?, what are the theoretical proposals for the segmentation of utterances?), and practical problems (where is the real border between the two utterances in spoken language?, what criteria of segmentation stream of spoken language can be used?). The language material – which is the basis for the research presented in this article – comes from twenty task-oriented dialogue sessions with the participation of forty speakers performing a specific task. As a result of the analysis, based on available positions and theoretical reflection I managed to develop a tool for syntactical segmentation of the stream of spoken language. This tool can be presented in the form of a new (innovative) concept of definition of the utterance.